Oligossacarídeos de rafinose em cana-de-açúcar: caracterização de genes sob estresse hídrico e abordagens transgênicas - Maniero, Rafael [UNESP] (2015)
Bioenergy application of sugarcane byproducts are making this crop one of the most important in the international agribusiness investments. To meet global demand and expand the sugarcane sector, genetic engineering strategies generating transgenic plants more tolerance to biotic and abiotic stresses is a promising to improve productivity. One of the most relevant mechanism related to stress tolerance in plants involves the accumulation of distinct solutes. The Raffinose Oligosaccharids Family synthesis starts from the successive addition of galactosyl radicals to a sucrose molecule, in a reaction catalyzed by galactinol synthase (GolS), raffinose synthase and stachyose synthase. GolS plays a key role in RFOs production in model plants. Although the stress-responsive action of RFOs may improve abiotic stress tolerance in plants, these mechanisms are almost completely unknown in grasses, like sugarcane. In this context, this study aims to understand molecular aspects of RFOs synthesis and its relation with abiotic stresses. We have evaluated the transcriptional level of genes related RFOs synthesis under water stress and we produced transgenic plants constitutively expressing a coffee galactinol synthase (CaGolS2). Under water stress, ScGolS1 was downregulated in leaves, but upregulated in stems. ScRFS1 and ScSTS1 were upregulated in both tissues, in a direct correlation between transcription level and stress. We produced 10 transgenic events containing the coding region of CaGolS2; in six events, the transgene were transcriptionally active. Transgenic plants presented differences in morphology and carbon assimilation when compared to non-transgenic controls. Overall, we inferred that the stress-responsive pattern of RFO synthesis genes might help carbon relocation during water stress. Raffinose and stachyose seems to have greater impact than galactinol in this process. Furthermore, CaGolS2 transgenic plants have promising traits for...